You need to use the following formulas for `sinh x` and `cosh x` such that:

`sinh x = (e^x - e^(-x))/2`

`cosh x = (e^x+e^(-x))/2`

`sinh x + cosh x = (e^x - e^(-x) + e^x+ e^(-x))/2`

Reducing like terms yields:

`sinh x + cosh x = (2e^x)/2 => sinh...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to use the following formulas for `sinh x` and `cosh x` such that:

`sinh x = (e^x - e^(-x))/2`

`cosh x = (e^x+e^(-x))/2`

`sinh x + cosh x = (e^x - e^(-x) + e^x+ e^(-x))/2`

Reducing like terms yields:

`sinh x + cosh x = (2e^x)/2 => sinh x + cosh x = e^x`

Substituting `e^x` for `sinh x + cosh x` yields:

`int_(-10)^10 (2e^x)/e^x dx = int_(-10)^10 2 dx`

`int_(-10)^10 2 dx = 2x|_(-10)^10`

`int_(-10)^10 2 dx = 2(10 - (-10)) = 2*20`

`int_(-10)^10 2 dx = 40`

**Hence, evaluating the given definite integral yields `int_(-10)^10 (2e^x)/(sinh x + cosh x) dx = 40.` **